ADAPTIVE INDONESIAN LANGUAGE LEARNING TO ISLAMIC BOARDING SCHOOL VALUES - Faizi, Ahmad; Hardinanto, Eko; Dwinata, Anggara; Indrawan, Fani; Asteria, Prima Vidya; Harfiandi, Harfiandi (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2024)
Adaptation to local values ​​is the choice of many parties when they want to bring justice to the classroom. This research reveals the cultural diversity adapted in Indonesian language learning, especially the typical Islamic boarding school values ​​of Mbh Hasyim Asy'ari Tebuireng. This research is ethnocritical. The data used is linguistic data in the form of teacher and student speech. Data collection was carried out using observation and interview methods. Data were analyzed using ethnocritical theory. Researchers describe the values ​​(culture) that exist in Indonesian language learning at Junior High Schools in Tebuireng. Apart from that, the researcher also provided critical comments on the data description. The findings in this research are that Indonesian language learning in Tebuireng is carried out in an active, integrative manner. As a result, there are three Islamic boarding school values ​​that are adapted in learning, namely: openness values, togetherness values, and tasamuh values. These values ​​are utilized by teachers to create active, interactive and loving learning.